New Data on the Copper Mineralization of the Pribrezhny Volcanic Complex of Southern Kamchatka - Vladimirtseva O.V.; Bergal-Kuvikas O.V.; Subbotin N.A.; Orlov S.Yu. (Pleiades Publishing, Ltd., 2025)
This paper reports new data on the copper mineralization in the Pribrezhny Volcanic Complex (PVC), which is a part of the Eastern Kamchatka–Kurile volcanic plutonic belt (part of the Kurile-Southern Kamchatka island-arc system). The study area is situated along the eastern coast of the southern Kamchatka Peninsula, from Avacha Bay to Mutnaya Bay. It was found that the majority of collected volcanic and intrusive rocks have the elevated copper contents compared to the clarke values. The sources of copper in the PVC rocks are debatable, and this paper considers its possible origin. The distribution of porphyry copper deposits on other island arcs of the Pacific Ring in similar tectonic settings highlights the need for searching similar deposits in the coastal band of southeastern Kamchatka. Based on the geology, structure, and composition of the PVC, the authors admit the principal possibility of the existence of unexposed porphyry copper systems. Obtained results could be used for substantiation of thematic prospecting.
Keywords: 38.49.19 Геология рудных месторождений